2021
DOI: 10.3390/curroncol28060456
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Diagnosis and Therapy of Angioimmunoblastic T Cell Lymphoma

Abstract: Angioimmunoblastic T cell lymphoma (AITL) is a common subtype of mature peripheral T cell lymphoma (PTCL). As per the 2016 World Health Organization classification, AITL is now considered as a subtype of nodal T cell lymphoma with follicular helper T cells. The diagnosis is challenging and requires a constellation of clinical, laboratory and histopathological findings. Significant progress in the molecular pathophysiology of AITL has been achieved in the past two decades. Characteristic genomic features have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 98 publications
0
21
0
5
Order By: Relevance
“…Management of patients with relapse/refractory (R/R) disease should include careful assessment of the patient’s eligibility for autologous stem cell transplantation (ASCT) [ 18 ], although this can be very challenging given the disease-related symptoms and comorbidities that most patients have [ 14 , 19 ]. Delivery of high-dose therapy (HDT) followed by ASCT (HDT-ASCT) is considered the standard of care for R/R lymphomas, including PTCL.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Management of patients with relapse/refractory (R/R) disease should include careful assessment of the patient’s eligibility for autologous stem cell transplantation (ASCT) [ 18 ], although this can be very challenging given the disease-related symptoms and comorbidities that most patients have [ 14 , 19 ]. Delivery of high-dose therapy (HDT) followed by ASCT (HDT-ASCT) is considered the standard of care for R/R lymphomas, including PTCL.…”
Section: Discussionmentioning
confidence: 99%
“…Delivery of high-dose therapy (HDT) followed by ASCT (HDT-ASCT) is considered the standard of care for R/R lymphomas, including PTCL. However, results are dismal in PTCL patients, with a relapse rate over 80% [ 18 , 20 ]. A multicenter study that evaluated long-term disease-free survival in 29 patients with AITL after HDT-ASCT found that 5-year overall and event-free survival were 44% and 37%, respectively [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Later, it was recognized as angioimmunoblastic T-cell lymphoma (AITL) in the revised European-American classification of lymphoid neoplasms (REAL) and World Health Organization (WHO) classifications [ 1 ]. It is a rare disease and accounts for approximately 15%-30% of peripheral nodal T-cell lymphomas (PTCL) globally and represents 2% of all non-Hodgkin’s lymphomas (NHLs) [ 1 , 2 ]. No consistent risk factors or etiological agents have been identified in AITL [ 1 ]; however, there is some association with Epstein-Barr virus (EBV) and several reports have shown that high EBV viremia upon presentation was associated with a worse response, disease progression, or evolution into aggressive B-cell lymphoma [ 2 ].…”
Section: Introductionmentioning
confidence: 99%